Penyelesaian Tindak Pidana Pengeroyokan Melalui Hukum Adat Gayo: Perspektif Hukum Pidana Islam - Asih Pertiwi; Santi Nurdani; Witriah Witriah; Dessy Asnita (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
The settlement of mobbing offenses through Gayo customary law in Gampong Padang Terangun, Gayo Lues Regency, has prioritized deliberation and Denne sanctions in the form of compensation of IDR 100,000 per perpetrator. This value is considered too low and disproportionate to the victim's suffering. This study asks whether the Denne sanction aligns with the principle of proportional justice in Islamic criminal law, particularly the concepts of diyat, arsy, dhaman, and the principle of isytirak fil jinayah. This research employs field research with a descriptive qualitative approach, drawing from interviews with Gecik, customary leaders, witnesses, and perpetrators of mobbing during June-July 2025, supported by scientific journals and relevant regulations. The findings show that the procedural mechanism of Gayo customary deliberation aligns with the principle of sulh in Islam, but the Denne sanction substantively fails to meet economic justice standards due to the absence of fixed benchmarks and its overly symbolic value. This study concludes that harmonization between Gayo customary law and the provisions of fiqh jinayah is necessary, particularly in determining the amount of compensation based on the type of injury suffered by the victim.